STUDY OF THE EFFECT OF SPRAYING WITH GROWTH STIMULANTS ROOTEX AND VAGE AMINO IN IMPROVING THE QUALITATIVE CHARACTERISTICS OF THE FRUITS OF ZIZIPHUS SPINA L. TREES - OLA AHMED NAJM; MAHMOUD S. ABDUL-WAHID (University of Thi-Qar Journal of agricultural research, 2025)
The research was carried out in a private orchard associated with Dhi Qar Governorate during the autumn season of 2024-2025 to examine the impact of spraying the growth stimulant Rootex and vage amino on enhancing the qualitative attributes of Ziziphus spina trees. Rootex was utilised at three concentrations (0, 1, and 2 g/L), whilst vage amino was employed at three concentrations (0, 1.5, and 0.3 ml/L). The experiment was conducted as a factorial study utilising the randomised complete block design (RCBD) with three replications. Upon conclusion of the trial, the statistical analysis yielded the following results: The application of 2 g/L of Rootex growth promoter shown superiority in average fruit length and drop, average fresh and dry weight of fruit, flesh and seed, and average pulp/seed ratio, yielding values of 2.55 cm, 2.41 cm, 11.28 g, 10.15 g, 1.36 g, and 7.37 g, respectively. The administration of 3 ml/L of vage amino growth promoter demonstrated superiority in average fruit length and drop, average fresh and dry weight of fruit, flesh and seed, and average pulp/seed ratio, yielding measurements of 2.67 cm, 2.53 cm, and 11.44. The interaction treatment demonstrated significant superiority, with the combination of Rootex at 2 gm/L and vage amino at 3 ml/L surpassing the average length and diameter of the fruit, as well as the average fresh and dry weight of both the flesh and seed, and the average pulp/seed ratio, yielding results of 2.85 cm, 2.71 cm, 12.96 gm, 11.99 gm, 1.46 gm, and 8.19 gm, respectively.